Towards a resilience management guideline — Cities as a starting point for societal resilience. (July 2019) - Marana, Patricia; Eden, Colin; Eriksson, Henrik; Grimes, Clara; Hernantes, Josune; Howick, Susan; Labaka, Leire; Latinos, Vasileios; Lindner, Rene; Majchrzak, Tim A.; Pyrko, Igor; Radianti, Jaziar; et al.
Highlights: Lack of operationalization frameworks for the development of resilience in cities. Co-creation process to involve city stakeholders is needed. Development of a resilience toolkit for cities. Development of an integrated management system for resilience building at the local level. Standardization to support the resilience development process. Abstract: Unexpected crises and risks affect the urban population. Critical infrastructure dependency, climate change and social dynamics have captured the attention of city decision makers across different disciplines, sectors, and scales. Addressing these challenges mandates an increase in resilience. This article presents the development of the novel European Resilience Management Guideline (ERMG) developed by the European H2020 Smart Mature Resilience (SMR) project. It encompasses five supporting tools for city resilience. The purpose of this article is threefold. First, it describes the extensive co-creation methods used to establish, validate and test the five ERMG tools as collaborations among seven city stakeholders and researchers in Europe. Second, it explains concisely the features of each tool and its use and applicability in the city resilience building process. Third, it shows how EMRG supports strategic management in encouraging the visibility of risk dependencies, identifying vicious loops and potential cascading effects, and promoting collaboration between stakeholders to share resources. The article concludes with a discussion of SMR standardization activities to support the transfer of these research results to wider audiences. It covers guidance on local resilience planning and supporting efforts in building and operationalizing resilience at the city level.